Antioxidant, DNA-damage protection and anti-cancer properties of n-butanol extract of the endemic Perralderia coronopifolia (Bangladesh Journal of Pharmacology, 2018)
This study was designed to evaluate in vitro the total phenolic, flavonoid content, antioxidant activity, oxidative DNA-damage protection and anti-cancer activity of n-butanol extract from Perralderia coronopifolia, endemic plant. DNA protection capacity was performed using 46966 plasmid DNA against UV-photolysis of H2O2-induced oxidative damage. The antiproliferative effects of extract were performed on HeLa and C6 cells. Experimental results showed that extract had convenient number of phenolic and flavonoids. Furthermore, it provided strong anti-oxidant, reducing power, hydrogen peroxide and higher DPPH· scavenging ability with IC50= 7.02 ± 0.02 µg/mL. As it shown an oxidative plasmid DNA-damage inhibition against UV-photolysis of H2O2, an anti-cancer activity athigher concentrations in cells. The data obtained that P. coronopifolia extract could be useful in human protection against infection and degenerative illness.Video Component of Methodology:Metal chelating activity:   2 min 56 sec   Click to watch